2016
DOI: 10.1002/syn.21893
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of [11C]TAZA for amyloid β plaque imaging in postmortem human Alzheimer's disease brain region and whole body distribution in rodent PET/CT

Abstract: Objective Alzheimer’s disease (AD) is a neurodegenerative disease characterized by Aβ plaques in the brain. The aim of this study was to evaluate the effectiveness of a novel radiotracer, 4-[11C]methylamino-4′-N,N-dimethylaminoazo-benzene ([11C]TAZA), for binding to Aβ plaques in postmortem human brain (AD and normal control (NC)). Methods Radiosyntheses of [11C]TAZA, related [11C]Dalene (11C-methylamino-4′-dimethylaminostyrylbenzene), and reference [11C]PIB were carried out using [11C]methyltriflate prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Displacement of [ 3 H]PIB by TAZA (Fig. 7) was greater than observed by CUR and is consistent with our previous findings of the high affinity of TAZA for Aβ plaques (Pan et al 2016). Compared to both CUR and TAZA, FA exhibited little displacement of [ 3 H]PIB, suggesting weaker affinity for Aβ plaques and is consistent with reported findings of FA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Displacement of [ 3 H]PIB by TAZA (Fig. 7) was greater than observed by CUR and is consistent with our previous findings of the high affinity of TAZA for Aβ plaques (Pan et al 2016). Compared to both CUR and TAZA, FA exhibited little displacement of [ 3 H]PIB, suggesting weaker affinity for Aβ plaques and is consistent with reported findings of FA.…”
Section: Discussionsupporting
confidence: 92%
“…7a), which was greater in the GM regions compared to WM regions with GM/WM ratio of ~2. In the presence of 4-methylamino-4'-N,N-dimethylaminoazobenzene (TAZA) (1 μM), which is known to bind to Aβ amyloid plaques with high affinity (Pan et al 2016), significant displacement of [ 3 H]PIB occurred from the GM regions (Fig. 7c), with GM/WM ratio reducing to 1:3.…”
Section: Resultsmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the most common type of dementia, accounting for 50 to 80 percent of dementia cases characterized by the accumulation of amyloid β (Aβ) plaques and neurofibrillary tangles (NFT) in the brain (Braak & Braak, 1991; Braak, Thal, Ghebremedhin, & Tredici, 2011). Several PET radiotracers have been developed for imaging of Aβ and some of them are currently in clinical use (Pan et al., 2016). Alongside progress in Aβ imaging, efforts have been underway on the development and use of NFT PET imaging agents (Lemoine et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…24 Different studies have reported on increased metabolic activity of BAT Uptake of 2-deoxo-2-18 F-Fluoro-D-Glucose( 18 F-FDG), In human BAT positron emission tomography / computed tomography (PET/CT) studies. [26][27][28] Simultaneously ways were found of examining BAT in rats with the use of 123+ I MIBG, that is an analog of norepinephrine, 29 followed by norepinephrine trasporters, which got visualized with the use of 11 C -Methyl reboxitine (MRB) and 11 30,31 Use of 11 C -acetate, 11 C-palmitate along with using radiolabelled fatty acids as metabolic substrates was done by other researchers. 32,33 For getting newer strategies to be able to act regarding obesity therapy it is important to be able to measure the metabolic activity of BAT.…”
Section: Role Of Ewing Sarcoma Protein (Ew S)/ Y Box Protein 1(ybx) /mentioning
confidence: 99%
“…30 Also 11 C-TAZA via the NET in the BAT along with IBAT and other BAT regions also gets taken up as is shown by PET. 31 Quantification of atomoxetine's effects on BAT metabolism was done using 18 F-FDG PET/CT recently. 81 Much more increase occurs as compared to ephedrine.…”
Section: Class 2-drugs Changing Norepinephrinementioning
confidence: 99%